The politics of time: Modernity and avant-garde - Osborne, Peter (London Verso Books, 1995)
If Aristotle sought to understand time through change, might we notreverse the procedure and seek to understand change through time? Oncewe do this, argues Peter Osborne, it soon becomes clear that ideas suchas avant-garde, modern, postmodern and tradition&which are usually onlytreated as markets for empirically discrete periods, movements orstyles&are best understood as categories of historical totalization.More specifically, Osborne claims, such ideas involve distincetemporalizations of history, giving rise to conflicting politics oftime.His book begins with a consideration of the main aspects ofmodernity and develops though a series of critical engagements with themajor twentieth-century positions in the philosophy of history. Heconcludes with a fascinating history of the avant-garde interventioninto the temporality of everyday life in surrealism, the situationistsand the work of Henri Lefebvre.